cAMP-CRP-activated E. coli causes growth arrest under stress conditions - Haque, Most Farzana; Tarusawa, Takefusa; Ushida, Chisato; Ito, Shion; Himeno, Hyouta (Frontiers in Microbiology, 2025)
Cells are exposed to various kinds of stress, obliging them to cope with the challenges they encounter. Upon subjecting E. coli cells to oxidative stress induced by elevated concentrations of hydrogen peroxide or plumbagin, as well as osmotic stress by elevated NaCl concentrations, cell growth stopped immediately after stress and it resumed after a period of time. In the present study, we found that the stress-induced growth arrest disappeared when the gene for cAMP synthesis (cyaA) or its receptor protein (crp) was deleted, whereas it reappeared when cAMP is exogenously added to ∆cyaA cells. With increasing stress intensity, the period of growth arrest increased in the wild-type cells, while ∆cyaA or ∆crp cells continued to grow without arrest, although their growth rates were reduced. These results indicate that E. coli cell has a novel cAMP-CRP-dependent mechanism to stop cell growth temporarily for adaptation to new environment when subjected to a strong stress, whether oxidative or osmotic stress.